Articles of War: Subjects and Objects Aboard the Nineteenth-Century Naval Novel. (1st September 2016) - Cook, Daniel
ABSTRACT: This essay engages the world of the nineteenth-century naval novel, considering how the 'wooden world' presented in such narratives came to shape a unique representational order. Taking Captain Frederick Marryat's The King's Own (1830) as primary evidence, it is argued that naval novels depict the man-of-war as a place where the things – and men – of the parlour and marketplace find themselves reconstituted as components of the 'Service'. This alternate order emerges in one of the most exhilarating features of high-seas thrillers: their recurrence to dense, largely un-translated nautical terminology. Such language foregrounds the man-of-war as a purely functional assemblage of parts, inviting the subject to die and become reborn as an object of state. At one level, this project was distinctly British. At the same time, the British fixation on naval gadgetry resonates with American and French naval novels of the period, cooperating in what arguably became a transnational militarism. Such narratives prepare the way for a modern ideological strategy by which warfare becomes ennobled on the basis of its economic sanctity.